2013
DOI: 10.7566/jpsj.82.014707
|View full text |Cite
|
Sign up to set email alerts
|

Crossover between BCS Superconductor and Doped Mott Insulator ofd-Wave Pairing State in Two-Dimensional Hubbard Model

Abstract: With high-Tc cuprates in mind, the properties of correlated d x 2 −y 2 -wave superconducting (SC) and antiferromagnetic (AF) states are studied for the Hubbard (t-t ′ -U ) model on square lattices using a variational Monte Carlo method. We employ simple trial wave functions including only crucial parameters, such as a doublon-holon binding factor indispensable for describing correlated SC and normal states as doped Mott insulators. The U/t, t ′ /t, and δ (doping rate) dependences of relevant quantities are sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
96
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 128 publications
16
96
0
Order By: Relevance
“…It has been shown that, in a wide range of the parameter space of concern, a d-SC state becomes stable compared with the projected Fermi sea (ordinary normal state). 35 …”
Section: Hubbard Modelmentioning
confidence: 99%
“…It has been shown that, in a wide range of the parameter space of concern, a d-SC state becomes stable compared with the projected Fermi sea (ordinary normal state). 35 …”
Section: Hubbard Modelmentioning
confidence: 99%
“…Here, P G is the fundamental onsite (Gutzwiller) projection, and P Q is a nearest-neighbor doublon-holon projection, which is indispensable for Mott physics [13,14]:…”
Section: Formalismmentioning
confidence: 99%
“…Main properties of these states have been already studied for eq. (1) [14,15]. Here, we do not introduce the band renormalization effect into the optimization, but for Ψ N , we can substantially allow for this effect within t , as will be explained in sec.…”
Section: Formalismmentioning
confidence: 99%
See 2 more Smart Citations